Practical Anesthetic Management : The Art of Anesthesiology - Larson Jr., C. Philip; Jaffe, Richard A. (Springer International Publishing : Imprint: Springer, 2017)
As Sir William Osler said "The practice of medicine is an art, based on science". The authors believe that the art of precision medicine is knowing when the science of medicine should not be applied to your patient. This practical guide to managing patient expectations while maintaining a good medical practice presents as one of the only books of its kind. Written for anesthesiology residents in training, as well as practicing physicians, Practical Anesthetic Management focuses on giving clinicians the tools to create safer, more effective and efficient practices while catering to patient satisfaction. Featuring pearls for teaching purposes, Practical Anesthetic Management also covers topics like preoperative evaluation, tips on blood-gas analysis, and essentials of airway management, all complete with accompanying videos. .
Keywords: Medicine.; Anesthesiology.; elektronické knihy; electronic books